Assessment and prevention of hypoglycaemia in primary care among U.S. Veterans: a mixed methods studyResearch in context - Scott J. Pilla; Kayla A. Meza; Mary Catherine Beach; Judith A. Long; Howard S. Gordon; Jeffrey T. Bates; Donna L. Washington; Barbara G. Bokhour; Anais Tuepker; Somnath Saha; Nisa M. Maruthur (Elsevier, 2023)
Summary: Background: Hypoglycaemia from diabetes treatment causes morbidity and lower quality of life, and prevention should be routinely addressed in clinical visits. Methods: This mixed methods study evaluated how primary care providers (PCPs) assess for and prevent hypoglycaemia by analyzing audio-recorded visits from five Veterans Affairs medical centres in the US. Two investigators independently coded visit dialogue to classify discussions of hypoglycaemia history, anticipatory guidance, and adjustments to hypoglycaemia-causing medications according to diabetes guidelines. Findings: There were 242 patients (one PCP visit per patient) and 49 PCPs. Two thirds of patients were treated with insulin and 40% with sulfonylureas. Hypoglycaemia history was discussed in 78/242 visits (32%). PCPs provided hypoglycaemia anticipatory guidance in 50 visits (21%) that focused on holding diabetes medications while fasting and carrying glucose tabs; avoiding driving and glucagon were not discussed. Hypoglycaemia-causing medications were de-intensified or adjusted more often (p < 0.001) when the patient reported a history of hypoglycaemia (15/51 visits, 29%) than when the patient reported no hypoglycaemia or it was not discussed (6/191 visits, 3%). Haemoglobin A1c (HbA1c) was not associated with diabetes medication adjustment, and only 5/12 patients (42%) who reported hypoglycaemia with HbA1c <7.0% had medications de-intensified or adjusted. Interpretation: PCPs discussed hypoglycaemia in one-third of visits for at-risk patients and provided limited hypoglycaemia anticipatory guidance. De-intensifying or adjusting hypoglycaemia-causing medications did not occur routinely after reported hypoglycaemia with HbA1c <7.0%. Routine hypoglycaemia assessment and provision of diabetes self-management education are needed to achieve guideline-concordant hypoglycaemia prevention. Funding: U.S. Department of Veterans Affairs and National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK).